Manajemen Perianestesi dengan Balanced Anestesi pada Pasien Operasi Laparoscopy Konversi Open Laparotomi Diagnosa Cholelithiasis dengan Anemia dan Trombositopenia : Studi Kasus - Abdurrahman, Muhammad Naufal; Pratama, Rizkian; Febrianti, Vita Ariska Devi; Handayani, Rahmaya Nova; Suandika, Made (Pustaka Galeri Mandiri, 2026)
Cholelithiasis with comorbid anemia and thrombocytopenia poses significant challenges in perioperative management, particularly when laparoscopic cholecystectomy must be converted to open laparotomy due to severe inflammation and adhesions. This case report describes the anesthetic management of a 57-year-old male patient diagnosed with cholelithiasis, anemia (Hb 10.8 g/dL), thrombocytopenia (96 ×10³/µL), and leukopenia, who underwent surgery under balanced general anesthesia. The procedure was initiated laparoscopically but converted to open laparotomy due to gallbladder wall thickening and distorted anatomy. Intraoperatively, bleeding of approximately 500 mL occurred, requiring transfusion of packed red cells and platelets. Hemodynamic fluctuations in the form of hypotension were successfully managed with fluid therapy and transfusion, ensuring adequate tissue perfusion. Postoperatively, the patient experienced delayed emergence, which improved following antagonization with atropine and neostigmine. The patient was subsequently transferred to the ICU for intensive monitoring given the risks associated with anemia, thrombocytopenia, and suboptimal recovery. This case highlights the importance of comprehensive preoperative evaluation, vigilant intraoperative monitoring, individualized anesthetic strategies with balanced anesthesia, and multidisciplinary collaboration to minimize complications in biliary surgery patients with hematological comorbidities